Analisis Yuridis Anak di Bawah Umur sebagai Pelaku Tindak Pidana Penyalahgunaan Narkotika Berdasarkan Undang-Undang Sistem Peradilan Pidana Anak - Muhammad Putra Syawal Al Mahdi; Boedi Prasetyo (Jurnal Hukum Lex Generalis, 2024)
Children have an important role as the nation's next generation, so the state is obliged to provide optimal support for their development. However, deviant behavior, including narcotics abuse, shows a significant increase, especially due to the influence of globalization and information technology. In a legal context, children involved in drug abuse may be considered offenders, although they should also be treated as victims who need rehabilitation, not prison sentences. One of them occurred in the Curup District Court Decision Number 00/Pid.Sus-Anak/2022/PN Crp, on January 3 2022, where Child I and Child II were suspected of being involved in narcotics abuse in Tanjung Aur Village. Arrests were made and all evidence was recognized as theirs, and examination showed that they controlled large amounts of narcotics without permission from the authorities. This research aims to explore the criminal responsibility of minors related to narcotics abuse and the appropriate forms of legal protection for them. In this research, the author uses a normative juridical research method using literature study and a legal approach. The research results show that the SPPA Law emphasizes restoration, rehabilitation and protection of children's rights through a restorative justice approach by resolving cases outside of court or diversion to restore relationships between children, victims and society. In an effort to protect children, the SPPA Law provides legal protection through guidance and rehabilitation, special procedures for handling children's cases, as well as regulating identity confidentiality. The role of community counselors, social workers and social welfare workers is very important as a form of legal protection for children, with a focus on recovery and reintegration into society.